1990
DOI: 10.1007/bf01200929
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of pulp and paper mill effluent by growth ofAspergillus niger

Abstract: Pulp and paper mill effluent was decolorized by growth ofAspergillus niger. Adding glucose (2.0 g/l) and NH4H2PO4 (1.0 g/l) improved decolorization by the fungus (leaving 19% of original colour) and reduced the BOD5 (43%) and the COD (41%) of the effluent after 48 h of incubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 2 publications
1
4
1
Order By: Relevance
“…The level of color reduction in the present study is below to these reports, but it is comparable with the C. versicolor in liquid culture this fungus removed over 60% of the color of combined bleach Kraft effluent within 6 days in the presence of sucrose (Livernoche et al 1983). However, the most important aspect of present study is that there was a very high reduction in the COD and BOD as compared to earlier report (Kannan 1990). …”
Section: Effluent Treatmentscontrasting
confidence: 54%
“…The level of color reduction in the present study is below to these reports, but it is comparable with the C. versicolor in liquid culture this fungus removed over 60% of the color of combined bleach Kraft effluent within 6 days in the presence of sucrose (Livernoche et al 1983). However, the most important aspect of present study is that there was a very high reduction in the COD and BOD as compared to earlier report (Kannan 1990). …”
Section: Effluent Treatmentscontrasting
confidence: 54%
“…3. These data are in agreement with other studies in which a critical amount (between 0.1 and 0.2%) of glucose was necessary to maintain the decolourization activity, but only low glucose consumption was observed [62]. This has led to the suggestion that /3-glucosidase production may play a key role in the efficiency of decolourization by fungi [63,64].…”
Section: Industrial Waste Water Treatmentsupporting
confidence: 92%
“…The colour and lignin reduced [27,[35][36][37]. The decolourization potential of these fungi varies greatly ranging from values above 90% to below 30%.…”
Section: Analysis Of Data and Confirmatory Experimentsmentioning
confidence: 99%
“…Another study showed 56% reduction in colour after treatment for 48 h using Aspergillus niger. Initial colour was 1000 CU [36]. Some of the studies have optimized the process parameters; however, they have not evaluated the improvement in the process after optimization.…”
Section: Analysis Of Data and Confirmatory Experimentsmentioning
confidence: 99%